Research on classroom teaching strategies for junior high school students under the guidance of core literacy - Zhong, Yujiao; Pereira, Jerito (CV. Pustaka Literasi Ilmiah, 2024)
Student-oriented classroom is the fertile ground for students to develop core literacy of mathematics. The new curriculum standard emphasizes the teaching concept of